Univariate stability analysis and relationship among parameters for grain yield of striga resistant sorghum [Sorghum bicolor (L.) Moench] hybrids in Ethiopia - Fantaye Belay; Firew Mekbib; Taye Tadesse (Open Journal of Plant Science - Peertechz Publications, 2021)
Sorghum (Sorghum bicolor) known as a Camel crop of cereals, is among the dominant staple food grains for the majority of Ethiopians. Forty nine sorghum genotypes (hybrids + open pollinated varieties) were tested at five locations in a simple lattice design with two replications during the 2016 main cropping season. The objectives of this study were to determine yield stability using univariate methods and to assess the association among stability parameters of striga resistant sorghum genotypes in the dry lowland areas of Ethiopia. The result of the combined analysis of variance for grain yield revealed highly significant (P≤0.001) difference among Environment (E), Genotype (G) and Genotype × Environment Interaction (GEI). Based on the combined ANOVA over locations, the mean grain yield of environments ranged from 588 kg ha-1 in Humera to 4508 kg ha-1 in Sheraro. The highest yield was obtained from ESH-1 (3278 kg ha-1), while the lowest was from K5136 (735 kg ha-1) and the average grain yield of genotypes was 2184 kg ha-1. Different stability models were used in measuring of genotype stability such as AMMI Stability Value (ASV), Yield Stability Index (YSI), coefficient of regression (bi) and deviation from regression (S2di). Yield was significantly correlated with bi (0.91), r2 (0.55) and ASV (-0.56), while it was not correlated with S2di (-0.26). The non-significant correlation among yield and stability statistics indicated that, stability statistics provide information that can not be collected from average yield. The high positive correlation among mean grain yield and stability parameters is expected as the values of these parameters were higher for high yielding genotypes and the vice versa. Highly correlated stability parameters indicate that they can measure stability similarly. However, there were inconsistencies with the univariate stability parameters used, which created uncertainty to select or recommend the stable genotypes. Therefore, as the data is from one year, it is necessary to repeat the experiment at least for one more year across diverse dry lowland areas of Ethiopia.